Pengaruh Religious Maturity (Kedewasaan Beragama) Terhadap Sikap Toleransi Masyarakat Muslim di Kota Depok - Badruddin; Muammar Zulfiqri (CV Kalimasada Group, 2025)
This study aims to examine the influence of religious maturity on the tolerance attitudes of the Muslim community in Depok City. Employing a mixed methods approach with a sequential explanatory design, quantitative data were collected through a survey of 384 respondents, while qualitative data were obtained through interviews and focus group discussions (FGDs). Statistical analysis revealed a significant positive correlation between religious maturity and tolerance attitudes (r = 0.573, p < 0.001). Simple linear regression showed that 32.9% of the variance in tolerance attitudes was explained by religious maturity (R² = 0.329), while multiple regression analysis identified the intellectual, consequential, and experiential dimensions as significant predictors. Moderation analysis indicated that education level, age, and religious affiliation strengthened the relationship, whereas gender had no significant effect. Qualitative findings identified four patterns of the relationship between religious maturity and tolerance, as well as various influencing factors, including education, socio-cultural context, media, and family. This study underscores the importance of fostering a comprehensive and transformative religious maturity to cultivate tolerant attitudes in a multicultural society. The findings are expected to serve as a foundation for developing inclusive policies based on universal religious values.